Say nothing : a true story of murder and memory in Northern Ireland - Keefe, Patrick Radden, 1976- (Doubleday, 2019)
"Meticulously reported, exquisitely written, and grippingly told, Say Nothing is a work of revelation." --David Grann, #1 New York Times bestselling author of Killers of the Flower Moon. From award-winning New Yorker staff writer Patrick Radden Keefe, a stunning, intricate narrative about a notorious killing in Northern Ireland and its devastating repercussions. In December 1972, Jean McConville, a thirty-eight-year-old mother of ten, was dragged from her Belfast home by masked intruders, her children clinging to her legs. They never saw her again. Her abduction was one of the most notorious episodes of the vicious conflict known as The Troubles. Everyone in the neighborhood knew the I.R.A. was responsible. But in a climate of fear and paranoia, no one would speak of it. In 2003, five years after an accord brought an uneasy peace to Northern Ireland, a set of human bones was discovered on a beach. McConville's children knew it was their mother when they were told a blue safety pin was attached to the dress--with so many kids, McConville always kept it handy for diapers or ripped clothes. Patrick Radden Keefe's mesmerizing book on the bitter conflict in Northern Ireland and its aftermath uses the McConville case as a starting point for the tale of a society wracked by a violent guerrilla war, a war whose consequences have never been reckoned with. The brutal violence seared not only people like the McConville children, but also I.R.A. members embittered by a peace that fell far short of the goal of a united Ireland, and left them wondering whether the killings they committed were not justified acts of war, but simple murders. From radical and impetuous I.R.A. terrorists--or volunteers, depending on which side one was on--such as Dolours Price, who, when she was barely out of her teens, was already planting bombs in London and targeting informers for execution, to the ferocious I.R.A. mastermind known as The Dark, to the spy games and dirty schemes of the British Army, to Gerry Adams, who negotiated the peace and denied his I.R.A. past, betraying his hardcore comrades--Say Nothing conjures a world of passion, betrayal, vengeance, and anguish"--